PROKRASTINASI AKADEMIK SISWA SMA NEGERI DI KABUPATEN NIAS SELATAN - Laia, Bestari; Zagoto, Sri Florina Laurence; Fau, Yohanna Theresia Venty; Duha, Agustinus; Telaumbanua, Kaminudin; Lase, ndah Permata Sari; Ziraluo, Merdina; Duha, Maria Magdalena; Laia, Baziduhu; Luahambowo, Baspuri; Fai, Sesilianus; Hulu, Fatolosa; Telaumbanua, Tatema; Harefa, Darmawan (Unversitas Katolik Santo Thomas, 2022)
The purpose of the study is to describe the academic procrastination of students and the factors that influence them. The type of research that qualitative research uses is a descriptive approach. Data collection techniques are observation, interview, and documentation. Research informants are teachers and students. The results showed that the form of academic procrastination of students is late to collect tasks, delay to start doing tasks, and delay learning time and factors that affect academic procrastination of students are internal factors that are lazy, boredom of tasks, unable to manage study time and external factors, namely parental parenting style factors, community environment and weather or Covid-19 situation.